Effectiveness of The Use Artificial Intelligence on Biology Student Learning UIN Syahada Padangsidimpuan - Dongoran, Misahradarsi; Nasution, Ummu Atikah; Pane, Dewi Akhiriah (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Artificial Intelligence or AI is one of the technological achievements that is changing the landscape in various sectors of human life. Along with the development of technology, AI is taking an important role in various aspects of life, including higher education. In this digital era, AI has become an important partner and tool for students in solving their “problems”. This study aims to see the effectiveness of using Artificial Intelligence (AI) in learning biology. The research method used is a quantitative descriptive method using a questionnaire, Likert Scale, which was made in google form and then sent to Whatsapp Group and students' private chat. By using random method 52 biology students from semester III, V and VII have participated in this study. The percentage of the results of this study shows that 13.46% of students very often, 67.31% often, 19.23% Sometimes 0% of students never use AI in their learning process, for students AI has become something commonplace in helping them do lecture assignments, find relevant material and information, work on practicum activity reports and field lectures and for the final level AI really helps them in doing their final lecture assignments such as proposals and theses.Keywords: Effective, Artificial Intelligence, Learning, Biology